Multiplexed detection of SARS-CoV-2 based on upconversion luminescence nanoprobe/MXene biosensing platform for COVID-19 point-of-care diagnostics. (November 2022) - Song, Menglin; Ma, Yingjing; Li, Lihua; Wong, Man-Chung; Wang, Pui; Chen, Jiangkun; Chen, Honglin; Wang, Feng; Hao, Jianhua
Graphical abstract: We developed label-free multiplexed RNA analysis strategy based on the weakening of the FRET effect between different emission UCNPs and broad-spectrum quencher Nb2 CTx to simultaneously detect ORF and N gene of SARS-CoV-2. Highlights: 2D Nb2 CTx nanosheets have the capability of quenching the fluorescence at wavelengths ranging from visible to near-infrared spectrum. Simple and label-free multiplexed RNA analysis strategy was developed. Upconversion luminescence nanoprobe/MXene biosensing platform enables rapid and sensitive detection of ORF and N gene of SARS-CoV-2 simultaneously. Abstract: Multiplexed detection is essential in biomedical sciences since it is more efficient and accurate than single-analyte detection. For an accurate early diagnosis of COVID-19, a multiplexed detection strategy is required to avoid false negatives with the existing gold standard assay. Nb2 CTx nanosheets were found to efficiently quench the fluorescence emission of lanthanide-doped upconversion luminescence nanoparticles at wavelengths ranging from visible to near-infrared spectrum. Using this broad-spectrum quencher, we developed a label-free FRET-based biosensor for rapid and accurate detection of SARS-CoV-2 RNA. To target ORF and N genes, two types of oligo-modified lanthanide-doped upconversion nanoparticles can be used simultaneously to identify-two sites in one assay via upconversion fluorescence enhancement intensity measurement with detection limits of 15 pM and 914 pM, respectively. Moreover, with multisite cross-validation, this multiplexed and sensitive biosensor is capable of simultaneous and multicolor analysis of two gene fragments of SARS-CoV-2 Omicron variant within minutes in a single homogeneous solution, which significantly improves the detection efficiency. The diagnosis result via our assay is consistent with the PCR result, demonstrating its application in the rapid and accurate screening of multiple genes of SARS-CoV-2 and other infectious diseases.